Improving Students' Artificial Intelligence Literacy through Hybrid Training in Supporting the Competency of the Society 5.0 Era - Supiyandi Supiyandi; Chairul Rizal; Irman Efendi; Muhammad Noor Hasan Siregar; Arief Wibowo (LKP KARYA PRIMA KURSUS, 2026)
This community service program aimed to improve university students’ Artificial Intelligence (AI) literacy through hybrid training that supports the competencies required in the Society 5.0 era. The rapid advancement of digital technology has increased the need for students to understand, utilize, and critically evaluate AI technologies in academic and professional contexts. The program was implemented using a hybrid learning approach that combined face-to-face and online learning activities through educational counseling, workshops, interactive discussions, and practical simulations of AI applications. The participants were university students who received training in basic AI concepts, ethical use of AI, digital literacy, and the implementation of AI technologies to support academic activities and twenty-first-century competencies. The instruments used in this activity included training modules, digital presentation media, observation sheets, and pre-test and post-test evaluations to assess participants’ understanding before and after the training sessions. The findings indicated that the hybrid training successfully improved students’ understanding of Artificial Intelligence, enhanced their ability to use AI technologies in academic activities, and increased their awareness of ethical and responsible AI use. Furthermore, the hybrid learning model provided flexible, interactive learning experiences that promoted active participation and strengthened students’ adaptability to the digital transformation in the Society 5.0 era. The program also demonstrated that AI literacy plays a significant role in supporting students’ readiness for technology-driven educational and professional environments. Therefore, hybrid AI literacy training can serve as an effective and relevant model for developing digital competencies in higher education and supporting the transformation of education in the Society 5.0 era.